An energy, environmental, management and economic analysis of energy efficient system towards renewable energy community: The case study of multi-purpose energy community. (1st October 2022) - Ceglia, F.; Esposito, P.; Faraudello, A.; Marrasso, E.; Rossi, P.; Sasso, M.
Abstract: The Renewable Energy Directive drives the European Countries to enhancement of independent energy systems and self-consumption users such as Renewable Energy Communities. The recent directives about energy communities represent a development of previous ones about energy sharing systems defined in the early 2000s. In this work, the past and current directives about energy sharing have been investigated by considering technical and management aspects. The social, economic, technical aspects of Renewable Energy Communities have defined in order to show the advantage of them and their upgrade with respect to previous energy sharing directives. In addition, a case study has been considered by using an energy, environmental and economic analysis in a multi-purpose energy community by considering three different configurations for end-users: simple users, energy close sharing system and energy community. The energy community loads and energy conversion systems have been modelled and simulated by using a commercial software. The results about community configuration by following recent directive show an annual electricity self-consumption index equal to 56%. The renewable energy community allows to avoid 39.5 t/y of CO2 emissions with respect to the traditional configuration without sharing approach. The index of renewable energy source local self-consumption of energy community results higher than the sharing system referred to previous directives. People involved in this community could be more aware for environment issues and they could develop a more sustainable attitude. Graphical abstract: Image 1 Highlights: Analysis of energy sharing directives during a decade for European Union and Italy. Management analysis of old and current energy sharing directives. Energy, environmental and economic analysis of a Renewable Energy Community. Comparison of Efficient Users' System and conventional single users.